(untitled) (Educação e Pesquisa, 2015)
This article discusses the importance and centrality that merit has in Chilean society today, focusing on its multidirectional relationships to the educational realm. Our argument will be developed in three steps. Firstly, we will present the historical context of the social transformations that are to be related with the expansion of the principle of merit in this society. Secondly, we will analyze the manners in which the recognition of merit is evaluated at each of the different stages of school trajectories by members of middle and popular sectors. Finally, we will describe and discuss the way in which, due to the maintained impact of social networks and interpersonal contacts, the expansion of merit is closely related to the emergence of a new horizon of social injustice. Consequently, the article evidences that, concerning the expansion of the principle of merit in Chile, we face a twofold process: the emergence of a strong consensus about the value of merit, and the widespread sentiments of injustice and frustration that it produces in individuals. This discussion is based upon the findings of two qualitative studies. The first one was developed between 2007 and 2009 in Santiago, Concepción and Valparaíso cities, in Chile. About one hundred interviews were held with men and women aged 30 to 55 years of middle and popular sectors. The second, an ongoing study, provided our analysis with sixteen interviews, which were carried out in Santiago in 2014, and enabled us to further analyze the merit theme.